International transactions in goods : global sales in comparative context - Davies, Martin, 1957-; Snyder, David V. (New York : Oxford University Press, 2014)
This study describes the law relating to the transactions involved in the international sale of goods. It does not confine itself to the law of the international sale contract, but deals also with the indispensable ancillary transactions relating to payments and transport. It is written from a comparative perspective, combining material from international law, common law, civil law, and the world of commerce. The book combines extensive explanatory text with illustrative excerpts from cases, legislation, and documents widely used in international trade.
Includes index.
Description based on online resource; title from home page (viewed on July 9, 2014).
Keywords: Export sales contracts